Descemet Stripping Endothelial Keratoplasty: Fifteen-Year Outcomes. Issue 4 (30th April 2023) - Price, Marianne O.; Price, Francis W.
Abstract : Purpose: The purpose of this study was to evaluate 15-year outcomes of Descemet stripping endothelial keratoplasty (DSEK). Methods: We retrospectively reviewed an initial, consecutive series of 350 DSEK cases in 290 patients (mean age 69 years), performed between December 2003 and December 2005 for Fuchs dystrophy (86%), pseudophakic/aphakic bullous keratopathy (10%), or failed penetrating keratoplasty (4%). Outcomes included best spectacle-corrected visual acuity (BSCVA), endothelial cell density (ECD), and graft failure (defined as regraft for any reason or persistent loss of stromal clarity). Results: At 15 years, 46 of 350 DSEK grafts (13%) had failed, 155 (44%) were in patients who died, and 84 of the remaining 149 grafts (56%) were examined. After accounting for loss to follow-up, the probability of graft failure was 7% at 5 years, 16% at 10 years, and 23% at 15 years. The main risk factor for late endothelial failure was preoperative glaucoma (hazard ratio: 4.4 for medically managed and 24 for surgically managed glaucoma). The probability of an immunologic rejection episode was 7% by 1 year, 14% by 10 years, and 17% by 15 years. The median donor ECD decreased from 3030 cells/mm 2 before DSEK to 1973 cells/mm 2 at 6 months (36% loss) and 705 cells/mm 2 at 15 years (78% loss). The median BSCVA, including the eyes with ocular comorbidity, was 20/60 preoperatively, 20/40 at 3 through 12 months, and 20/30 from 2 to 15 years. Conclusions: DSEK provided excellent long-term visual rehabilitation and graft survival in this early cohort, performed when the technique was still being refined.